The effect of SPADA-integrated electronic civic education teaching materials on improving students' STEM and communication skills - Sumardi, Lalu; Fadli, Adi; Fauzan, Ahmad (Journal of Education and e-Learning Research, 2025)
This study aims to measure the effectiveness of electronic civic education teaching materials integrated into LMS-SPADA in improving students' STEM reasoning ability and communication skills. In addition, this study will also measure the effect of gender on their STEM reasoning ability and communication skills. The research design is a quasi-nonequivalent pre- and post-tests control group design. The sample size is 60 students consisting of 24 male and 36 female. An essay test was used to collect data on STEM reasoning skills. Meanwhile, communication skills were collected using a questionnaire. The data were analyzed descriptively and using a t-test. This study found that students' STEM reasoning and communication skills can be improved by using civic education electronic teaching materials integrated into LMS-SPADA (learning management system-SPADA). Another finding of this study is that gender significantly affects students' STEM and communication skills where male students are better at STEM reasoning than female students, while female students are better in the aspect of communication skills. Therefore, it is clear that electronic civic education materials integrated into LMS-SPAD are effective in improving students' STEM reasoning and communication skills.